Seismotectonics of Sri Lanka—insights from the first island-wide temporary network - Christian Haberland; Mahinda Seneviratne; Trond Ryberg; Karl-Heinz Jäckel (Earth, Planets and Space)
Abstract In 2016 and 2017, we operated a temporary broadband seismic network with 30 stations in Sri Lanka, the first covering almost the entire island, to obtain a detailed overview on the seismicity and the deeper structure. Three permanent seismic stations complemented the network. Earthquakes were automatically detected, and in total we could analyze 256 local events. 100 events could be identified as local earthquakes, 156 as artificial blasts mainly related to the construction of 2 dams. A high-quality subset of the data was first used for a simultaneous inversion for the one-dimensional velocity model, precise earthquake locations and station corrections utilizing a hierarchical, transdimensional Markov chain Monte Carlo inversion routine. All events were then accurately relocated and hypocenter uncertainties derived. Seismicity is mainly found in the southeast part of the study area, however, isolated seismicity is distributed across the Island. For the first time also the hypocenter depths of the island-wide seismicity were derived, which are found in the top 15 km as well as in a deeper band around 25 km depth. We speculate that the earthquakes occur on reactivated older fractures and faults present throughout the island, and that deeper earthquakes could be possible due to the expected cold and dry old crust of Sri Lanka. Local magnitudes (ML) range between 0.4 and 2.6. Focal mechanisms, which could be calculated for 6 events, have predominantly strike–slip mechanism with a roughly north–south-oriented P-axis. This is consistent with the current north–south-oriented stress regime in the Indian subcontinent, and faults and fractures with corresponding orientations that may have been reactivated have previously been mapped in Sri Lanka. The 1-D velocity model is rather typical for continental crust, starting with 6.1 km/s at the surface and jumping to 6.6 km/s at around 18 km depth, and a pronounced low Vp/Vs layer between 6 and 18 km depth. The velocity structure indicates felsic to intermediate rocks with intermediate to high silica content. Graphical Abstract